Cases in leadership - "Rowe, W. Glenn; Guerrero, Laura" (New Delhi, 2016)
The updated Fourth Edition helps business students gain a better understanding of leadership enabling them to be more effective leaders through their careers. Key features: Real-world cases from around the world illustrate the complex nature of leadership in organizations and aide in the application of concepts to a practical setting Concept summaries, discussion questions, and readings for each chapter provide students with a solid framework for understanding key leadership theories
Keywords: Leadership